THE IMPORTANCE OF DYNAMIC PLAY ADDRESSING MUSIC AS AN INVESTIGATIVE APPROACH - Pasăre Daniela; Vizitiu Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
This study presents the opinion of some specialists in the field of physical education and sports regarding the importance of dynamic plays addressing music, and the modality in which those are used in the benefit of education. There were five questions formulated to emphasize the familiarity with the term of'' play'' or ''dynamic play'', what the dynamic plays represent, what role those plays have in the sports activity, and what impact may have those dynamic plays while playing music, on the students personality. From the view of the statistical investigation of the answers regarding the questions addressed to teachers show low interest using plays and music, the preparation being based on the principles, methods and traditional means, occupying a place with priority in the educational process.